2019
DOI: 10.1029/2018jd029658
|View full text |Cite
|
Sign up to set email alerts
|

All‐Sky Assimilation of the MWHS‐2 Observations and Evaluation the Impacts on the Analyses and Forecasts of Binary Typhoons

Abstract: Satellite data assimilation is transitioning from clear‐sky to all‐sky approach at some operational forecasting centers; the all‐sky approach directly assimilates observations under clear, cloudy, and precipitating conditions and shows a positive impact on medium‐range forecasts. Although there has been progress in the all‐sky technique for the forecasting of high‐impact weather processes, such as typhoon, these studies mainly focused on a single typhoon case, and the influence of all‐sky assimilation on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The typical approach for all-sky radiance assimilation at most operational centers is to use observation error inflation. 137 A number of studies for TC all-sky MW radiance assimilation employing similar error model formulations [126][127][128][129] suggested positive impacts on TC predictions. A similar observation error model to account for the cloud amount for the direct assimilation of all-sky infrared radiances was developed as well.…”
Section: Treatment Of Observation Errormentioning
confidence: 99%
See 1 more Smart Citation
“…The typical approach for all-sky radiance assimilation at most operational centers is to use observation error inflation. 137 A number of studies for TC all-sky MW radiance assimilation employing similar error model formulations [126][127][128][129] suggested positive impacts on TC predictions. A similar observation error model to account for the cloud amount for the direct assimilation of all-sky infrared radiances was developed as well.…”
Section: Treatment Of Observation Errormentioning
confidence: 99%
“…Regional assimilation of all‐sky radiances generally presents a different challenge (e.g., domain size, model top, bias correction, etc.) compared to the global assimilation; however, several demonstration studies showed the feasibility of the all‐sky microwave assimilation in the regional models, and overall resulted in positive impacts on TC track, intensity, storm structure, and precipitation forecasts 126–129 …”
Section: Tc Observationsmentioning
confidence: 99%
“…An apparently positive impact has been reflected in temperature and relative humidity in the AL and DY experiments (Figures 5(a ). e reasons for these negative impacts are not clearly, but some studies [35,36] have also addressed this situation. ey indicated that other advanced data assimilation approaches, such as hybrid (ensemble/3D-VAR) or 4D-VAR method, will deal with this problem as these advanced data assimilations can provide flow-dependent ensemble background covariance error which is not achieved in the 3D-VAR data assimilation.…”
Section: Rmse �mentioning
confidence: 99%
“…A better description of the tropical cyclone thermodynamic fields under the all‐sky condition allows for reasonable deep convective triggering and development, thus leading to an improved representation of rapid intensification through the assimilation cycle (Kazumori & Kadowaki, 2017; Tong et al., 2020; Zhang et al., 2021). In addition to these impacts, all‐sky MW radiance assimilation also improves the tropospheric wind fields, resulting in better midlatitude atmospheric circulation and improves TC track prediction (Xian et al., 2019; Yang et al., 2016; Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the typical difficulties shared by the direct assimilation of radiances, such as large uncertainties and biases in the Radiative Transfer Model for cloud absorption and scattering (Li et al., 2016; Okamoto, 2017), the inconsistency between the simulated hydrometeors and observations (Barlakas et al., 2021), and high nonlinearity for the cloudy radiance (Errico et al., 2007), direct assimilation of cloud‐affected IR, near‐IR, and VIS radiances suffers from the significant challenge of the high sensitivity of Jacobian to clouds (Li et al., 2016; Vidot et al., 2015). In addition, most of the channels currently used for IR imager all‐sky assimilation are water vapor channels, making the thermodynamic information updated but not the cloud due to the lack of direct observations (e.g., Candy & Migliorini, 2021; Geer et al., 2019; Lee et al., 2020; Shahabadi & Buehner, 2021; Xian et al., 2019; Zhang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%